(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
The quality of the brewed coffee depends on various factors. Resting time of roasted coffee beans is one of the processes that can affect the sensory charac- teristics of coffee brew. During resting the reduction of CO2 gas level may change and give significan effect on sensory quality of coffee. This study aims to determine the dominant sensory characteristics that can be used as quality parameters of cold brew coffee products at various resting times after roasting. The cold brew coffee product was brewed from roasted Arabica coffee beans with various resting time (0, 1, 3, 5, 7, and 9 days). Projective Mapping (Napping) sensory analysis method was used in this study. The samples were tested by 75 untrained panelists (naive panelists). Multiple Factor Analysis was used to obtain the cold brew coffee sample position configuration. The results of the analysis showed that panelists were able to differen- tiate the characteristic of sensory attributes each sample. The aroma and flavor are the main attributes that can differentiate the characteristics of each sample. From the napping method, the results obtained in the form of individual factor map and preference mapping showed that the sample resting time 1 and 3 days after roasting were assessed by the panelists as closest to the control sample (0 days). In summary, the resting time treatment of roasted coffee beans have a significant effect on the sensory characteristics of cold brew coffee products. This is proofed by changes of aroma, flavor, and aftertaste during certain period of resting time.